2005
DOI: 10.1103/physrevb.72.153403
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and dissociative adsorption of multiple hydrogen molecules on transition metal decoratedC60

Abstract: Recently we have predicted [Phys. Rev. Lett. May 2005] that Ti-decorated carbon nanotubes can absorb up to 8-wt% hydrogen at ambient conditions. Here we show that similar phenomena occurs in light transition-metal decorated C60. While Sc and Ti prefers the hexagon (H) sites with a binding energy of 2.1 eV, V and Cr prefers double-bond (D) sites with binding energies of 1.3 and 0.8 eV, respectively. Heavier metals such as Mn, Fe, and Co do not bond on C60. Once the metals are absorbed on C60, each can bind up … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
101
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 251 publications
(106 citation statements)
references
References 25 publications
3
101
1
1
Order By: Relevance
“…We discarded the case of the bond with a pentagonal ring, since the calculation predicts one imaginary frequency. These results disagree with those obtained by Yildirim et al (2005) that using the supercell and a pseudopotential approximation, reported that the Ti adsorbed on the hexagonal ring is the most stable one. Nevertheless, our results are consistent with the known capacity of transition metals to bind to the (6,6) bond (Mathur et al 1998;Shin et al 2006).…”
Section: Theoretical Methods and Computational Detailscontrasting
confidence: 57%
See 1 more Smart Citation
“…We discarded the case of the bond with a pentagonal ring, since the calculation predicts one imaginary frequency. These results disagree with those obtained by Yildirim et al (2005) that using the supercell and a pseudopotential approximation, reported that the Ti adsorbed on the hexagonal ring is the most stable one. Nevertheless, our results are consistent with the known capacity of transition metals to bind to the (6,6) bond (Mathur et al 1998;Shin et al 2006).…”
Section: Theoretical Methods and Computational Detailscontrasting
confidence: 57%
“…The number of studies of new nanostructures (Zhao et al 2005;Iñiguez et al 2007;Yildirim et al 2005;Bauschlicher et al 2002;Zope et al 2009;Zhang et al 2000;Yoon et al 2008;Yang et al 2009;Lee et al 2008;Durgun et al 2008;Koh et al 2011, Kiran et al 2006 able to absorb H 2 in at least 9 wt% have increased in the last years, following the goal proposed by the US Department of Energy of developing a system with this net gravimetric capacity for hydrogen storage. Among the different materials under consideration, systems composed by C 60 compounds coated with transition metals are between the most promising ones.…”
Section: Introductionmentioning
confidence: 99%
“…Such metals are known to interact with the σ * -antibonding of the hydrogen molecules strongly, destabilizing dihydrogen structure against classical hydride formation. Our preliminary results based on a structural optimization starting from t80TiH 2 -3H 2 with Ti replaced by Pt/Pd indeed indicate that the side hydrogen molecules are not bonded and leave the system immediately [24]. We did observe that two H 2 do indeed bind to Pt/Pd forming a PtH 4 (or PdH 4 ) classical hydride cluster, which was not bonded to the nanotube.…”
mentioning
confidence: 92%
“…However we expect the light transition metals like Sc and V to show similar behavior since they have both occupied and empty d-orbitals with a similar IP to Ti. We are currently investigating a large number of transition metals and the results will be published elsewhere [24].…”
mentioning
confidence: 99%
“…Recently, a novel concept to overcome these obstacles has been suggested [7][8][9][10][11][12][13][14]. It was predicted that a single Ti atom affixed to carbon nanostructures, such as C 60 or nanotubes, strongly adsorbs up to four hydrogen molecules [7,8,10].…”
mentioning
confidence: 99%